A feminist defense of pornography - McElroy, Wendy (Free Inquiry, 1997)
Keywords: approches et analyses; cours; intersectionnalité; point de vue situé; pornographie; premier cycle; ressource en ligne; sex1911; sexualité; thématiques

Generations & geographies in the visual arts: feminist readings - Pollock, Griselda.. (Routledge, 1996)
In Generations and Geographies, the challenge of contemporary feminist theory encounters the provocation of the visual arts made by women in the twentieth century. The major issue is difference: sexual, cultural and social. Generations points to the singularity of each artist's creative negotiation of time and historical and political circumstance; Geographies calls attention to the significance of place, location and cultural diversity, connecting issues of sexuality to those of nationality, imperialism, migration, diaspora and genocide.Generations and Geographies is framed by theoretical debates in cultural analysis by Griselda Pollock, Mieke Bal, Elisabeth Bronfen and Irit Rogoff, and two historical analyses of representations of the female nude by Rosemary Betterton and Nanette Salomon. Essays on international contemporary art discuss artistic practice by women working in both western and non-western contexts, focusing on themes of the mother, the body, the land and history/memory. The artists discussed include the French performance artist Orlan, the Cuban American artist Ana Mendieta and Jenny Saville from Britain, the Chilean artist Cecilia Vicuna, Shimada Yoshiko from Japan, the Korean artist Re-Hyun Park and the Korean/Canadian artist Jin-me Yoon, Bracha Lichtenberg Ettinger from Israel and the American artist Cindy Sherman. British/Zanzibari artist Lubaina Himid provides specially commissioned artists' pages on the theme of history, location and displacement.
Keywords: 1900-1999; approches et analyses; arts; arts visuels et médiatiques; corps; cours; discipline; har4600; histoire de l'art; histoire et politique; intersectionnalité; maternité; point de vue situé; premier cycle; périodes historiques; ressource en ligne; thématiques

What are friends for?: feminist perspectives on personal relationships and moral theory - Friedman, Marilyn (Cornell University Press, 1993)
A contribution to the feminist discussion on moral theory, exploring the debate between moral impartiality and the partiality that characterizes personal relationships, the ethic of care and its relation to justice in a gender asymmetrical society, and the role of intimate friendship in an era of the dissolution of both extended and nuclear families.
Section: 1 v. (xi-276 p.) ; 23 cm
Keywords: 1900-1999; 1980-1989; amour; amérique du nord; amériques; approches et analyses; care; cours; discipline; phi2030; philosophie; point de vue situé; premier cycle; périodes historiques; rapports sociaux de sexe; relations amoureuses; régions géographiques; sciences humaines; thématiques; états-unis; éthique

Whose science? Whose knowledge?: Thinking from women's lives - Harding, Sandra G. (Cornell University Press, 1991)
Sandra Harding here develops further the themes first addressed in her widely influential book, The Science Question in Feminism, and conducts a compelling analysis of feminist theories on the philosophical problem of how we know what we know.Following a strong narrative line, Harding sets out her arguments in highly readable prose. In Part 1, she discusses issues that will interest anyone concerned with the social bases of scientific knowledge. In Part 2, she modifies some of her views and then pursues the many issues raised by the feminist position which holds that women's social experience provides a unique vantage point for discovering masculine bias and and questioning conventional claims about nature and social life. In Part 3, Harding looks at the insights that people of color, male feminists, lesbians, and others can bring to these controversies, and concludes by outlining a feminist approach to science in which these insights are central. "Women and men cannot understand or explain the world we live in or the real choices we have," she writes, "as long as the sciences describe and explain the world primarily from the perspectives of the lives of the dominant groups."Harding's is a richly informed, radical voice that boldly confronts issues of crucial importance to the future of many academic disciplines. Her book will amply reward readers looking to achieve a more fruitful understanding of the relations between feminism, science, and social life.
https://books.google.ca/books?id=nXR6DQAAQBAJ&printsec=frontcover&hl=fr&source=gbs_ViewAPI&redir_esc=y#v=onepage&q&f=false
Keywords: approches et analyses; cours; discipline; fem1000; point de vue situé; premier cycle; rapports sociaux de sexe; ressource en ligne; sciences humaines; épistémologie

The Decade show: frameworks of identity in the 1980s - Young, Louis; New Museum of Contemporary Art (New York, N.Y.); Studio Museum in Harlem; Museum of Contemporary Hispanic Art (New York, N.Y.) (Museum of Contemporary Hispanic Art, 1990)
The Decade Show is a provocative examination of artistic production in the 1980s, embracing 113 artists and artists’ groups (including Ida Applebroog, Luis Cruz Azaceta, Gran Fury, Edgar Heap-Of-Birds, Komar & Melamid, Adrian Piper and Shu Lea Cheang) who - whether visible or invisible in the mainstream - are critical to an understanding of the period. Fourteen essayists, among them David Deitcher, Thelma Golden, Julia P. Herzberg, Micki McGee, Sharon F. Patton, Susan Quist and Lowery Stokes Sims, contribute to this extensive survey. As a collaborative effort between the Museum of Contemporary Hispanic Art, The New Museum and The Studio Museum in Harlem, The Decade Show reflects true community diversity, as well as the museum’s interest in examining “parallel cultures” obscured by traditional aesthetics. “This is not a patronizing exhibit of the art of ‘exotica’ put together by the philanthoropic goodwill and high-art-world curiosity of a few white curators. It is an exhibit attempting to construct a multivocal art world. It begins to suggest that the notion of a ‘center’ and a ‘margin’ is anachronistic and that maintaining such a model represents a desire to wield exclusive power and control.” -Eunice Lipton, “Here Today, Gone Tomorrow,” p. 20.
Section: 364 pages : illustrations (certaines en couleur)
Keywords: amériques; approches et analyses; arts; cours; discipline; har4610; histoire de l'art; intersectionnalité; point de vue situé; premier cycle; queer; régions géographiques; états-unis

The science question in feminism - Harding, Sandra G. (Cornell University Press, 1986)
Can science, steeped in Western, masculine, bourgeois endeavors, nevertheless be used for emancipatory ends? In this major contribution to the debate over the role gender plays in the scientific enterprise, Sandra Harding pursues that question, challenging the intellectual and social foundations of scientific thought.Harding provides the first comprehensive and critical survey of the feminist science critiques, and examines inquiries into the androcentricism that has endured since the birth of modern science. Harding critiques three epistemological approaches: feminist empiricism, which identifies only bad science as the problem; the feminist standpoint, which holds that women's social experience provides a unique starting point for discovering masculine bias in science; and feminist postmodernism, which disputes the most basic scientific assumptions. She points out the tensions among these stances and the inadequate concepts that inform their analyses, yet maintains that the critical discourse they foster is vital to the quest for a science informed by emancipatory morals and politics.
https://books.google.ca/books?id=27TrCuk4LRgC&printsec=frontcover&hl=fr&source=gbs_ViewAPI&redir_esc=y#v=onepage&q&f=falseSection: 271 p
Keywords: approches et analyses; cours; discipline; fem1000; point de vue situé; premier cycle; rapports sociaux de sexe; ressource en ligne; sciences humaines; épistémologie

Learning from the outsider within: The sociological significance of black feminist thought - Hill Collins, Patricia (Social Problems, 1986)
Keywords: afro-féminisme; amériques; approches et analyses; cours; discipline; fem1000; féminismes noirs; intersectionnalité; point de vue situé; premier cycle; ressource en ligne; régions géographiques; sciences humaines; sociologie; thématiques; épistémologie; états-unis

Discovering reality : feminist perspectives on epistemology, metaphysics, methodology, and philosophy of science - Harding, Sandra G.; Hintikka, Merril B. (D. Reidel, 1983)
This collection of essays, first published two decades ago, presents central feminist critiques and analyses of natural and social sciences and their philosophies. This work provides a splendid opportunity for upper-level undergraduate and graduate students in philosophy and the social sciences to explore some of the most intriguing and controversial challenges to disciplinary projects and to public policy today.
Keywords: approches et analyses; cours; discipline; discours dominant; fem1000; philosophie; point de vue situé; premier cycle; sciences humaines; systèmes d'oppressions; épistémologie

The feminist standpoint: Developing the ground for a specifically feminist historical materialism - Hartstock, Nancy (Discovering reality: Feminist perspectives on epistemology, metaphysics, methodology, and philosophy of science, 1983)
Keywords: approches et analyses; cours; discipline; fem1000; féminisme matérialiste; philosophie; point de vue situé; premier cycle; sciences humaines; épistémologie

Visions partielles, visions partiales: visions des minoritaiers en sociologies - JUTEAU-LEE, Danielle (Sociologie et sociétés, 1981)
Résumé L'irruption du discours des minoritaires en sociologie fait éclater le discours des majoritaires en provoquant la remise en question de leurs explications à tendance naturaliste, culturaliste et psychologisante. Affichant le caractère partiel et partial de leurs visions, les femmes et les "ethniques" favorisent l'éclosion de synthèses provisoires, susceptibles de rendre compte des formes multiples de l'oppression
Keywords: approches et analyses; cours; discipline; histoire et politique; intersectionnalité; patriarcat; point de vue situé; pol4212; premier cycle; racisme; sciences humaines; sexisme; sociologie; système colonial; systèmes d'oppressions; thématiques; universalisme